Figurative lights: Images of Techno-Scientific slides and Secularization in Spain during the 18th Century Las luces figuradas. Imágenes de dispositivos tecno-científicos y secularización en la España del siglo XVIII: retratos, linternas mágicas y globos - Germán LABRADOR MÉNDEZ (Cuadernos Dieciochistas)
This paper asembles and studies a set of iconological representations linked to technical and scientific transformations during the eighteenth Century in Spain, reading them in a dialectic between modern science, Enlightenment policies and popular culture. After analyzing the emergence of representations both of science and scientists according to the process of institutionalizing science as a socio-professional language, two specific eighteenth century technologies are studied: magic lanterns and aerostats. By interpreting their first images and their infiltration into popular and official speeches and the imagination of the moment, it is argued that in those images a tale of demo-Enlightenment is expressed, a tale about secularization and progress as a collective aesthetic experience. Este trabajo reúne y estudia una serie de representaciones iconológicas vinculadas a las transformaciones técnico-científicas del siglo XVIII español, leídas en una dialéctica entre ciencia moderna, política ilustrada y cultura popular. Tras analizar la emergencia de las representaciones de lo científico y de los científicos en relación con el proceso de institucionalización de la ciencia como lenguaje socioprofesional, se estudian dos tecnologías específicas de aquel siglo: la linterna mágica y el globo aerostático. A partir de la interpretación de sus primeras imágenes y de su infiltración en los discursos e imaginarios ilustrados y populares del momento, se defiende que en ellas se expresa un relato demoilustrado sobre la secularización y el progreso como experiencia estética colectiva.